(untitled) (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
This paper analyzes the relations between image and text in the Iberian funerary epigraphy. The incorporation of epigraphic language into the Iberian sepulchral discourse did not take place until the second century BCE; first, the text coexists with an iconography of an old tradition but, gradually, the text gained prominence over it until it became the only message of the monument.